(untitled) (Research, Society and Development, 2021)
The aim of the present article was to search for scientific evidence to evaluate the function and action of stevioside in patients with mellitus diabetes type 2. This work is an integrative literature review, the sources were linked in the following databases: (Scielo), (PubMed), LILACS and Academic Google. It was chosen some selection for the present sample and criteria for original articles indexed from 2017 to 2021 were established. The choice of this period presented results to the criterion of temporality, in which the five-year selected period was considered, as these are more current publications, in English and Portuguese in the studies analyzed, it was evidenced that stevioside is a glycosidic compound with high sweetness, low caloric value, including the interaction with glimeripedine and metformin, which enhances glycemic reduction through antioxidant actions and improves the lipid profile. It highlighted the action in reducing glucose and total cholesterol levels, preventing oxidative damage and improving liver and kidney function, as well as reducing damage to internal organs through removing tissue collagen and contributing to normal cardiac functioning. It also demonstrates positive results in satiety, contributing to a delay in gastric emptying and being useful in the treatment of obesity, working in the inhibition of glucose absorption. According this database, it is concluded that stevioside has preventive and metabolic function, besides to promote pre-clinical and experimental studies, culminating in non-caloric, anti-diabetic and anti-hyperglycemic effects, with sensory, therapeutic and nutritional quality.